Direct and indirect effects of ant–trophobiont interactions on the reproduction of a hummingbird-pollinated mistletoe - Ferreira, Vanessa C. M.; Neves, Frederico S.; Guerra, Tadeu J. (Plant ecology, 2022)
Fluid-feeding herbivores directly affect host plants through sap consumption. Moreover, they establish mutualistic relationships with ants, which might generate additional reproductive costs related to pollinator repellence. Here we studied the drivers of variation in the outcomes of these interactions from the perspective of Psittacanthus robustus , a hummingbird-pollinated mistletoe. We hypothesized that associations between fluid-feeding insects and ants should indirectly decrease mistletoe reproduction by repelling pollinators, and directly by reducing seed size, germination, and establishment of plants presenting denser herbivore aggregations. First, we manipulated the presence of the ant Camponotus rufipes on mistletoe inflorescences to assess their effects on visitation behavior of pollinators. We correlated fruit production and fruit and seed size to abundance of fluid-feeding insects on plants. Moreover, we conducted a field experiment assessing the effects of aggregation size of fluid-feeding herbivores on seed germination and seedling establishment. Ant presence on inflorescences did not affect the visitation rates of the main pollinator, the hummingbird Eupetomena macroura . Abundance of fluid-feeding herbivores did not explain variation in fruit crop size. However, we observed a significant reduction in seed size in those plants hosting larger aggregations of fluid-feeding herbivores. The reduction in seed size did not translate into a significant decrease in seed germination nor a decrease in seedling establishment. Our results dispute previous studies highlighting negative indirect effects on plant–pollinator interactions mediated by the presence of ant–trophobiont mutualisms. Likewise, our study underscores the need of assessing fluid-feeding herbivore effects on crucial stages of the host plant life cycle to clarify fitness consequences of multitrophic interactions.